New records of interesting xenophytes in the Iberian Peninsula. V - Sánchez Gullón, Enrique; Verloove, Filip (Lazaroa, 2015)
As a continuation of previous research on the naturalization of non-native vascular plants in the Iberian Peninsula new chorological data are presented for 16 xenophytes recorded between 2010 and 2014, mostly in the provinces of Huelva and Barcelona (Spain) and in the Algarve and Estremadura (Portugal). For each taxon details about distribution, habitats occupied, previous records, degree of naturalization, etc. are provided. Lachenalia bulbifera and Cyperus albostriatus are probably reported for the first time in the wild in Europe, as are Gamochaeta filaginea, and Dysphania anthelmintica and Oenothera lindheimeri for Portugal and Spain respectively. Cosmos bipinnatus is cited as a novelty for the Algarve (Portugal). Newly reported or confirmed for the province of Huelva are: Amaranthus hypochondriacus, Epilobium brachycarpum, Nephrolepis cordifolia, Ficus microcarpa, Tamarix parviflora and Tamarix ramosissima, while Atriplex semibaccata, Chloris truncata, and Elymus elongatus subsp. ponticus are new for Barcelona. Finally, Passiflora caerulea is a novelty for both Barcelona and Huelva provinces.